Modifying capillary pressure and boiling regime of micro-porous wicks textured with graphene oxide. (5th January 2018) - Jo, Hong Seok; An, Seongpil; Nguyen, Xuan Hung; Kim, Yong Il; Bang, Boo-Hyoung; James, Scott C.; Choi, Jeehoon; Yoon, Sam S.
Highlights: A highly porous wicking surface was introduced to promote capillary-driven flow in a heat pipe. Micro-porous copper coated with graphite oxide (GO) increased the critical heat flux. The thin GO layer promotes hydrophilicity that enhances the wettability of the wicking surface. Narrowed pores due to the GO layer increase the capillary pressure and the wicking effects. Abstract: Liquid flow inside a heat pipe due to capillary forces can be used to cool electronic devices. To promote capillary-driven flow, a multilayer, porous wicking surface was designed for optimal liquid transport. The multilayer-porous structure consists of micro-porous structure decorated with nanomaterials. Herein, we demonstrate that micro-porous copper coated with graphene oxide (GO) has elevated capillary forces that can increase both the critical heat flux and the convective heat transfer coefficient. The thin GO layer promotes hydrophilicity that enhances the wettability of the wicking surface. However, an excessively thick GO coating can decrease permeability even in the presence of increased capillary pressures such that overall flow is hindered. In this work an optimal coating thickness is identified and characterized by heat-transfer experiments and scanning electron microscopy.